Veterinary Drug Residues in Food Products of Animal Origin and Their Public Health Consequences: A Review - Yeshambel Muluye Mesfin; Birhan Agmas Mitiku; Habtamu Tamrat Admasu (Veterinary Medicine and Science)
Abstract Veterinary medications used for disease treatment and prevention may remain in animal‐origin foods, such as milk, eggs, honey and meat, which could pose a risk to the public's health. These drugs come from different groups of drugs, mostly with antibiotic, anti‐parasitic or anti‐inflammatory actions, in a range of food matrices including milk, meat or egg. This review is intended to provide the reader with a general insight about the current status of veterinary drug residues in food products of animal origin, detection methods and their public health consequences. The discovery of antimicrobials has led to the development of antibiotics for treating and preventing cattle illnesses and encouraging growth. However, the rise of drug resistance has led to increased antibiotic consumption and resistance among microbes in the animal habitat. This resistance can be passed to humans directly or indirectly through food consumption and direct or indirect interaction. Improper and illegal use, inadequate withdrawal periods and environmental contamination from veterinary drugs are reported to be the major causes for the formation of residue in food products of animal origin. The use of veterinary products above or below the advised level may also result in short‐ or long‐term public health issues, such as the creation of resistant strains of micro‐organisms, toxicity, allergy, mutagenesis, teratogenicity and carcinogenetic effects. To ensure consumer safety, veterinary drug residues in food must be under control.